2013
DOI: 10.1101/cshperspect.a012914
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Instability in Cancer

Abstract: One of the fundamental challenges facing the cell is to accurately copy its genetic material to daughter cells. When this process goes awry, genomic instability ensues in which genetic alterations ranging from nucleotide changes to chromosomal translocations and aneuploidy occur. Organisms have developed multiple mechanisms that can be classified into two major classes to ensure the fidelity of DNA replication. The first class includes mechanisms that prevent premature initiation of DNA replication and ensure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
160
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(170 citation statements)
references
References 132 publications
(144 reference statements)
5
160
0
2
Order By: Relevance
“…Rereplication can be induced experimentally through genetic inactivation of components of the CRL4 CDT2 complex (e.g., through CDT2 depletion or knockdown by siRNA), through CDT1 activation (e.g., by knockdown of geminin, a small protein inhibitor of CDT1), or through the activation of the APC/C CDC20 E3 ligase (e.g., by knockdown of the APC inhibitor EMI1; refs. 11,26). Finally, the discovery that treatment of cancer cells with the neddylation inhibitor pevonedistat (also known as MLN4924) inhibits cancer cell lines and tumors and is associated with significant induction of rereplication demonstrated that rereplication can be induced pharmacologically, and this may have an anticancer activity (27)(28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rereplication can be induced experimentally through genetic inactivation of components of the CRL4 CDT2 complex (e.g., through CDT2 depletion or knockdown by siRNA), through CDT1 activation (e.g., by knockdown of geminin, a small protein inhibitor of CDT1), or through the activation of the APC/C CDC20 E3 ligase (e.g., by knockdown of the APC inhibitor EMI1; refs. 11,26). Finally, the discovery that treatment of cancer cells with the neddylation inhibitor pevonedistat (also known as MLN4924) inhibits cancer cell lines and tumors and is associated with significant induction of rereplication demonstrated that rereplication can be induced pharmacologically, and this may have an anticancer activity (27)(28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%
“…This is mediated primarily through the targeted proteolysis of the replication licensing protein CDT1, the CDK inhibitor p21, and the histone methyltransferase SET8 during the S-phase of the cell cycle (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). CRL4 CDT2 is also activated, and its substrates are degraded, following DNA damage, such as that induced by ionizing radiation (IR), and this is important for PCNA-dependent DNA repair, and for IR-induced early G 2 -M checkpoint (11,26). CRL4 CDT2 -mediated ubiquitylation of CDT1, SET8, and p21 in the S-phase of unperturbed cells prevents reinitiation of DNA replication, a phenomenon termed DNA rereplication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in sporadic cancers, genomic instability is a consequence of DNA damage and alteration in DNA replication due to deregulation of the related genes in addition with impaired DNA repair (Anderson 2001, Negrini et al 2010. Therefore, DNA repair mechanisms play crucial role in cancer prevention through maintaining genomic stability and DNA integrity (Abbas et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Endocrine disruptors fall into six categories of chemicals including pesticides (DDT and methoxychlor), fungicides (vinclozolin), herbicides (atrazine), industrial chemicals (PCBs, dioxins), plastics (phthalates, bisphenol A, alkylphenols) and plant hormones (phytoestrogens) [1]. The most important assigned effect for the endocrine disruptors is genomic instability, defined as an increased tendency of the genome to acquire mutations [2]. It occurs when various processes involved in maintaining the genome are dysfunctional or when exposure to carcinogenic chemicals occurs [3].…”
Section: Introductionmentioning
confidence: 99%